Answer:
Step-by-step explanation:
g(x) = x^2 + 6
f(x^2 + 6) = 2(x^2 + 6) + 1 = 2x^2 + 12 + 1 = 2x^2 + 13
HELP YALL ILL GIVE BRAINLY
Answer: 78
Step-by-step explanation: multiply 39 by 2
Given:
The two points are (-2,3) and (-4,-2).
To find:
The gradient of the line segment between the given points.
Solution:
The gradient is also known as slope.
The slope formula:
The endpoints of the line segment are (-2,3) and (-4,-2). So, the gradient of the line is
Therefore, the gradient of the given line segment is .
Answer:
Option A is the answer
Step-by-step explanation:
In the figure attache a solid straight line has been drawn at y = 2 and the area above this line will be represented by y ≥ 2
Similarly area below the dotted line will be y < x
Now area which is common to both is colored area in blue.
So, the system of equations will be y ≥ 2 and y < x
Option A. is the answer.
Answer:
A
Step-by-step explanation: